2008
DOI: 10.1177/0002764207307745
|View full text |Cite
|
Sign up to set email alerts
|

The Racialization of Crime and Punishment

Abstract: The current explosion in criminalization and incarceration is unprecedented in size, scope, and negative consequences—both direct and collateral—for communities of color. These macro systems exist in relationality to the micro dynamics of living in the midst of police scrutiny, economic marginalization, and political disenfranchisement. Critical race theory is a guide for pedagogy and praxis in exploring the racist and classist foundations of current micro and macro injustices. Using Supreme Court opinions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(38 citation statements)
references
References 4 publications
0
33
0
Order By: Relevance
“…Thus, when we use the term structural racism, we refer to a social system in which race is a central principle of social organization that serves to sort individuals into positions of relative advantage and disadvantage based on their racial category. Research has shown how structural racism permeates nearly every important social institution in the United States (Reskin, 2012) such as criminal justice (Brewer & Heitzeg, 2008), financial markets (Cohen, 2013), health and medicine (Lukacho, Hatzenbuehler, & Keys, 2014), and the economy (Marable, 1983).…”
Section: Racialized Social Structure and Fundamental Causesmentioning
confidence: 99%
“…Thus, when we use the term structural racism, we refer to a social system in which race is a central principle of social organization that serves to sort individuals into positions of relative advantage and disadvantage based on their racial category. Research has shown how structural racism permeates nearly every important social institution in the United States (Reskin, 2012) such as criminal justice (Brewer & Heitzeg, 2008), financial markets (Cohen, 2013), health and medicine (Lukacho, Hatzenbuehler, & Keys, 2014), and the economy (Marable, 1983).…”
Section: Racialized Social Structure and Fundamental Causesmentioning
confidence: 99%
“…These theoretical analyses, along with empirical studies, point to the inescapable fact that racism remains an enduring reality of U.S. society. Scholars have highlighted ongoing racial inequities in housing (Lipsitz, 2006;Oliver & Shapiro, 2006), health care (Feagin & Bennefield, 2014) and the criminal justice system (Alexander, 2010;Brewer & Heitzeg, 2008;Davis, 1998). Some have also applied critical race theory to examine how institutional racism affects the educational opportunities and experiences of racialized students in the U.S. context (e.g., Dixson & Rousseau Anderson, 2018;Howard, 2008).…”
Section: Racism In the United States: A Theoretical And Empirical Rmentioning
confidence: 99%
“…The term ''anti-Black'' or ''antiblack'' racism is used with considerable regularity by race scholars throughout a wide variety of disciples. I see it most often in the social sciences, including Giroux (2003); Bobo, Kluegel, and Smith (1997); Muhammad (2010); and Brewer and Heitzeg (2008), who wrote, ''whereas all communities of color suffer from racism in general and its manifestation in criminal justice in particular, 'Black' has been the literal and figurative counterpart of 'White.' Anti-Black racism is arguably at the very foundation of White supremacy'' (p. 627).…”
Section: Conclusion: Messiah No Morementioning
confidence: 99%